Conceptual Framework for Non-hierarchical Business Networks for Complex Products Design and Manufacturing - Carneiro, Luis Maia; Cunha, Pedro; Ferreira, Pedro Sena; Shamsuzzoha, Ahm (My University, 2013)
The effective creation and management of business networks is more and more an important contribution for the competitiveness and sustainability of European SMEs. In Non-hierarchical networks SMEs join their competencies and resources to grab profitablebusiness opportunities. In these networks SMEs take the leading role and control the business instead of being subcontracted bylarge companies and traditional supply chains. This paper presents a conceptual framework, including methodological approach, best practices and reference processes aiming at supporting SMEs in creating and managing non-hierarchical networks for complexproducts design and manufacturing. The framework high level structure and the most specific processes are presented, including:capacity management, collaborative operations planning, risk and event management and performance management. The framework was validated in three pilot networks, from the textile, footwear and machine tools industries.
Keywords: Non-hierarchical business networks; Conceptual Framework; Reference processes; fi=Tuotantotalous|en=Industrial Management|